Depatuxizumab mafodotin in EGFR-amplified newly diagnosed glioblastoma: A phase III randomized clinical trial. Issue 2 (15th July 2022) - Lassman, Andrew B; Pugh, Stephanie L; Wang, Tony J C; Aldape, Kenneth; Gan, Hui K; Preusser, Matthias; Vogelbaum, Michael A; Sulman, Erik P; Won, Minhee; Zhang, Peixin; Moazami, Golnaz; Macsai, Marian S; et al.
Abstract: Background: Approximately 50% of newly diagnosed glioblastomas (GBMs) harbor epidermal growth factor receptor gene amplification ( EGFR -amp). Preclinical and early-phase clinical data suggested efficacy of depatuxizumab mafodotin (depatux-m), an antibody–drug conjugate comprised of a monoclonal antibody that binds activated EGFR (overexpressed wild-type and EGFRvIII-mutant) linked to a microtubule-inhibitor toxin in EGFR -amp GBMs. Methods: In this phase III trial, adults with centrally confirmed, EGFR -amp newly diagnosed GBM were randomized 1:1 to radiotherapy, temozolomide, and depatux-m/placebo. Corneal epitheliopathy was treated with a combination of protocol-specified prophylactic and supportive measures. There was 85% power to detect a hazard ratio (HR) ≤0.75 for overall survival (OS) at a 2.5% 1-sided significance level (ie traditional two-sided p ≤ 0.05) by log-rank testing. Results: There were 639 randomized patients (median age 60, range 22–84; 62% men). Prespecified interim analysis found no improvement in OS for depatux-m over placebo (median 18.9 vs. 18.7 months, HR 1.02, 95% CI 0.82–1.26, 1-sided p = 0.63). Progression-free survival was longer for depatux-m than placebo (median 8.0 vs. 6.3 months; HR 0.84, 95% confidence interval [CI] 0.70–1.01, p = 0.029), particularly among those with EGFRvIII- mutant (median 8.3 vs. 5.9 months, HR 0.72, 95% CI 0.56–0.93, 1-sided p = 0.002) or MGMT unmethylated (HR 0.77, 95% CI 0.61–0.97; 1-sided p = 0.012) tumors but without an OS improvement. Corneal epitheliopathy occurred in 94% of depatux-m-treated patients (61% grade 3–4), causing 12% to discontinue. Conclusions: Interim analysis demonstrated no OS benefit for depatux-m in treating EGFR -amp newly diagnosed GBM. No new important safety risks were identified.